Making Sense of Alternative Assessment in a Qualitative Evaluation System (2017)
In a Colombian private English institution, a qualitative evaluation system has been incorporated. This type of evaluation poses challenges to students who have never been evaluated through a system that eliminates exams or quizzes and, as a consequence, these students have to start making sense of it. This study explores the way students face the new qualitative evaluation system and their views on alternative assessment as a way to help them make headway with their English learning process.